A rare presentation of Mycobacterium africanum after two decades: a case report from Brunei Darussalam - Rubel, Abdur Rahman; Kishore, Panduru Venkata; Hla Aye, May Thu; Hafneh, Nor Azian; Chong, Vui Heng (Western Pacific Surveillance and Response, 2022)
Mycobacterium africanum is endemic to West Africa and is rare outside this region. Most of the people infected with M. africanum outside Africa are migrants from affected parts of Africa. We report a rare case of pulmonary tuberculosis (TB) secondary to M. africanum in a man in Brunei Darussalam who had lived and worked in Guinea, West Africa for 6 years more than 20 years ago. He had been well until December 2020, when he presented with a chronic cough and was diagnosed with coinfections of Klebsiella pneumoniae and M. africanum, and newly diagnosed diabetes mellitus. This case highlights an interesting manifestation of pulmonary TB secondary to M. africanum in a patient whose last exposure was 20 years ago, contributed to by development of diabetes mellitus.
Keywords: pulmonary tuberculosis; Mycobacterium tuberculosis complex; latency; Mycobacterium africanum